T cell cholesterol efflux suppresses apoptosis and senescence and increases atherosclerosis in middle aged mice - Venetia Bazioti; Anouk M. La Rose; Sjors Maassen; Frans Bianchi; Rinse de Boer; Benedek Halmos; Deepti Dabral; Emma Guilbaud; Arthur Flohr-Svendsen; Anouk G. Groenen; Alejandro Marmolejo-Garza; Mirjam H. Koster; et al. (Nature Communications, 2022)
Cholesterol efflux is mediated by specific transporters in T cells. Here the authors show that when the ABCA1/ABCG1 cholesterol transporters are absent, peripheral T cell numbers are reduced but activation increased with a premature aging phenotype of T cell senescence and apoptosis in middle aged Ldlr −/− mice.